2022
DOI: 10.3390/ijerph191811707
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Facilitators and Barriers for Actual Arm Use during Everyday Activities in Community Dwelling Individuals with Chronic Stroke

Abstract: Background: Our aim was to gain a deeper understanding of perceived predictors for actual arm use during daily functional activities. Methods: Qualitative study. Semi-structured interview data collected from individuals with chronic stroke living in the community. Codebook thematic analysis used for the data analysis. Results: Six participants 5–18 years post stroke with moderate to severe UE impairment. Three domains were identified: Person, Context, and Task. Themes for the Person domain included mental (cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The ultimate goal of this research is to improve actual arm use, defined as the spontaneous use of the affected UE in real world situations [ 67 ]. The results of this study will advance the scientific knowledge for UE rehabilitation because the use of MI and EMA as methods for enhancing adherence and engagement in UE self-training is a novel application.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate goal of this research is to improve actual arm use, defined as the spontaneous use of the affected UE in real world situations [ 67 ]. The results of this study will advance the scientific knowledge for UE rehabilitation because the use of MI and EMA as methods for enhancing adherence and engagement in UE self-training is a novel application.…”
Section: Discussionmentioning
confidence: 99%
“…Participants with PSD may have experienced decrease in active daily routines, and less energy to invest the extra (cognitive or physical) effort needed to use their affected UE in everyday activities, factors which have been reported to facilitate UE daily-use. 8 Since there were significant between-group differences at T3, we further categorized the participants into 4 subgroups to take into account participants with consistent PSD status and those who experienced changes in PSD status by T3. Participants who always had PSD or converted into PSD by T3 had the worst performance for all UE outcome measures compared to participants who never had PSD or converted out of PSD by T3.…”
Section: Discussionmentioning
confidence: 99%
“…7 Daily-use of the affected UE, also termed real-world use and actual arm use, is defined as the spontaneous integration and use of this UE in the real-world. 8 From the perspective of individuals with stroke, daily-use is considered the most important indicator for UE recovery. 9 Previous studies have identified motor and sensory deficits as key factors that contribute to daily-use of the affected UE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A weaker relationship between the FMA and the MAL-AOU (r s 0.35), but comparably high correlations for MAL-QOM (r s 0.76) were shown in a cross-sectional study including 223 individuals 89 . High variability of associations with perceived arm use may be related to the individual and cultural context 90 .…”
Section: Concurrent Validitymentioning
confidence: 99%